2005
DOI: 10.1111/j.0022-202x.2005.23843.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Macroscopic Fluorescence and Protoporphyrin IX Content in Psoriasis and Actinic Keratosis Following Application of Aminolevulinic Acid

Abstract: In fluorescence diagnosis with 5-aminolevulinic acid (ALA)-induced porphyrins (FDAP), protoporphyrin IX (PpIX) accumulation can be macroscopically visualized. Interpretation of these data is still problematic because of the low reproducibility of the procedure and poor understanding of the mechanisms involved in PpIX tumor selectivity. In this study, PpIX accumulation is investigated in patients with psoriasis and actinic keratosis (AK) following FDAP. For this purpose, desquamated lesional and non-lesional sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 25 publications
2
45
0
Order By: Relevance
“…When excited with light in the regions of 505 or 540 nm, protoporphyrin IX has an emission in the region of 635 nm. Studies measuring the ALA-elicited accumulation of protoporphyrin IX in tissues developed for the detection of cancerous cells have consistently found that the observed increase in fluorescence emission at 635 nm was closely associated with the accumulation of protoporphyrin IX in the tissue studied (30). Increases in protoporphyrin IX were measured using an excitation wavelength of 485 Ϯ 20 or 528 Ϯ 20 nm and emission of 620 Ϯ 40 nm in intact vessels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When excited with light in the regions of 505 or 540 nm, protoporphyrin IX has an emission in the region of 635 nm. Studies measuring the ALA-elicited accumulation of protoporphyrin IX in tissues developed for the detection of cancerous cells have consistently found that the observed increase in fluorescence emission at 635 nm was closely associated with the accumulation of protoporphyrin IX in the tissue studied (30). Increases in protoporphyrin IX were measured using an excitation wavelength of 485 Ϯ 20 or 528 Ϯ 20 nm and emission of 620 Ϯ 40 nm in intact vessels.…”
Section: Methodsmentioning
confidence: 99%
“…Although measurements of protoporphyrin IX fluorescence in tumor and normal cells also detect fluorescence from its biosynthetic precursors uroporphyrin III and coproporphyrin III, the ratios of these porphyrins appear to be similar across a variety of cell types (27). Thus tissue protoporphyrin IX fluorescence after treatment with ALA has been demonstrated in many studies to be closely associated with measurements of its levels in tissue extracts (30). The photosensitizing action of the protoporphyrin IX accumulated during exposure to ALA has also been developed as a phototherapy approach to kill tumors and other proliferating cells.…”
mentioning
confidence: 98%
“…2(d)] is very different with respect to protoporphyrin IX spectrum that has a peak at 630 nm. 49 In fact the emission spectrum of the hESC granules is very broad and it has a peak at 500 nm [ Fig. 2(d)].…”
Section: Identification Of the Intrinsic Biomarkers Inmentioning
confidence: 99%
“…In the past, we demonstrated a negative correlation between thickness of the stratum corneum and fluorescence intensity (in fluorescence diagnosis with ALA-induced porphyrins), indicating hyperkeratosis to be an important factor in intra- and interpatient differences in ALA uptake [1,2,3]. Pretreatment of the hyperkeratosis and the corneal layer is an important prerequisite for improving treatment results.…”
Section: Introductionmentioning
confidence: 99%